FEATURES OF SPREAD LEPTINOTARSA DECEMLINEATA SAY, 1824 INVAZIV TYPES IN FERGHANA VALLEY (Scientific journal of the Fergana State University, 2022)
The article describes the arrival and distribution directions of Leptinotarsa decemlineata Say1824which is considered a serious invasive pest, in the Fergana Valley. L.decemlineata is one of the 6 seriously invasive species identified in the valley region. Leptinotarsa decemlineata Say, 1824 type spread along Rishton → Central Fergana along the Fergana valley; Uzbekistan → Central Fergana; Fergana (district) → Central Fergana; It spread in the direction of Kosonsoy → Central Fergana.The directions of invasive species entering Central Fergana, their distribution characteristics, as well as the role and importance of food resources, temperature, humidity, light, as well as anthropogenic factors in the expansion of their areas are important.In the conditions of the Fergana Valley, the Colorado potato beetle can be found in morning potato agrocenoses from the second ten days of March to mid-June, and in evening potatoes from the first days of August to mid-October. This species easily adapts to the desert area and remains viable. This species reproduces 3 times in the conditions of the Fergana Valley.